Liver cirrhosis etiology, pathogenesis and clinical aspects - Salerno, Francesco
This book explains about the Cirrhosis that is a slowly progressing disease in which healthy liver tissue is replaced with scar tissue, eventually preventing the liver from functioning properly. The scar tissue blocks the flow of blood through the liver and slows the processing of nutrients, hormones, drugs, and naturally produced toxins